Hop tests correlate with IKDC and KOOS at minimum of 2 years after primary ACL reconstruction - Reinke, Emily K. (2011)
PURPOSE: The hypothesis of this study was that single-legged horizontal hop test ratios would correlate with IKDC, KOOS, and Marx activity level scores in patients 2 years after primary ACL reconstruction. METHODS: Individual patient-reported outcome tools and hop test ratios on 69 ACL reconstructed patients were compared using correlations and multivariable modeling. Correlations between specific questions on the IKDC and KOOS concerning the ability to jump and hop ratios were also performed. RESULTS: The triple-hop ratio was moderately but significantly correlated with the IKDC, KOOS Sports and Recreation subscale, and the KOOS Knee Related Quality of Life subscale, as well as with the specific questions related to jumping. Similar but weaker relationship patterns were found for the single-hop ratio and timed hop. No significant correlations were found for the Marx activity level or crossover-hop ratio. Multivariable modeling showed almost no significant additional contribution to predictability of the IKDC or KOOS subscores by gender, BMI, or the number of faults on either leg. CONCLUSIONS: The triple-hop test is most significantly correlated with patient-reported outcome scores. Multivariable modeling indicates that less than a quarter of the variability in outcome scores can be explained by hop test results. This indicates that neither test can serve as a direct proxy for the other; however, assessment of patient physical function by either direct report using validated outcome tools or by the hop test will provide relatively comparable data. LEVEL OF EVIDENCE: II.